Comparative Study of X-Ray and Sonographic Findings in Pneumonia in a Tertiary Hospital: A Cross-Sectional Study in Nepalese Adults - Umesh Khanal; Shailendra Katwal; Dik Prasad Kattel; Anamika Jha; Roshan Shrestha (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Pneumonia poses a signiﬁcant global health concern, particularly in developing nations, necessitating accurate and accessible diagnostic methods. Chest x-ray is the conventional imaging modality, albeit with radiation exposure risks. Lung ultrasonography offers a radiation-free alternative and is increasingly used for pneumonia diagnosis, especially in critical care settings. This study aimed to compare the diagnostic capabilities of chest x-ray and lung ultrasonography in nepalese adults with pneumonia, focusing on sensitivity in detecting speciﬁc pneumonia features such as consolidation with air bronchogram and pleural effusion. MATERIAL AND METHODS A cross-sectional observational study was conducted at a tertiary hospital in Nepal between September 2022 and September 2023. Participants clinically diagnosed with pneumonia underwent both chest x-ray and lung ultrasonography within 24 hours. Data on demographics, symptoms, physical examination, and imaging results were collected and statistically analyzed. RESULTS Among 77 participants, predominantly males with a mean age of 54.86 years, pneumonia was detected in 98.7% and 96.1% of cases through ultrasound and x-ray respectively. Ultrasonography exhibited superior sensitivity in identifying consolidation with air bronchogram (67.5% vs. 45.5%) and pleural effusion (55.8% vs. 31.2%) compared to x-ray. Statistical analysis showed signiﬁcant differences in the detection of consolidation with air bronchogram (p=0.0005) and pleural effusion (p=0.002) between the two modalities. CONCLUSION Lung ultrasonography demonstrates comparable or superior sensitivity to chest x-ray in detecting pneumonia, particularly in identifying speciﬁc features. Its radiation-free nature and bedside applicability make it a valuable diagnostic tool, especially in resource-limited settings.